Pengaruh LKPD berbasis saintifik pada pembelajaran model discovery learning terhadap hasil belajar IPA peserta didik kelas VIII di SMPN 30 Padang - Aulia Rahman (PILLAR OF PHYSICS EDUCATION, 2020)
There are many efforts to ge improvement on student’s learning outcomes. For instance by using teaching material and learning model choosing appropriately. So, it can increase the student’s learning activity. The purpose of this research is to know the influence of using LKPD scientific based into discovery learning model towards the result of student’s study science at eight grade students of SMPN 30 Padang. This research categorized as Quasi Experimental with randomized control group only design. The population that is used was all of the eight grade students on academic year 2018/2019. The sample is considered by purposive sampling technique. The data of knowledge and skill competencies achievement obtained by performances assesment sheet. The data of knowledge and skill compeencies achievement analyzed by similarituly of two average test. The result of this sudy showed that the using of LKPD scientific based into discovery learning model influential owards the student’s science learning outcomes at eight grade students of SMPN 30 Padang in knowledge and skill competencies. It can be seen on the acquisition score of experimental class is better than control class.